Social ecological approach to factors influencing perinatal mental health service provision among providers in Bulloch County, GA. (16th March 2023) - Choongo, Janet; Apenteng, Bettye; Nkemjika, Stanley; Telfair, Joseph
ABSTRACT: Perinatal mental illness pertains to pregnancy-related mental health complications, which could last as long as one year post-delivery. Despite the high prevalence of PMI, there remains a poor accessibility and utilization of mental health services, especially in the rural America. Hence, using the Social Ecological Model (SEM), we aim to identify factors influencing perinatal mental health service provision among providers in Bulloch County, GA. Using a random sampling method, we recruited 15 mental health providers in Bulloch County through professional networks who completed open-ended surveys between January 31 and March 5 of 2021. The open-ended survey was guided by the SEM constructs, which included Individual, Interpersonal, Organizational, Community, and Policy factors. The Qualitative thematic analysis was conducted using NVivo software. Major barriers among providers include lack of available resources and lack of rapport among patients and providers. Major facilitator themes included increase in mental health screening, rapport building, education, and awareness. This study suggests the introduction of group therapies in public communal areas is helpful. Findings from this study will be useful in developing tailored interventions to address barriers to perinatal mental health-care utilization experienced by both women and perinatal mental health-care providers.